Improving Students Character Using Fairy Tales - Martono Martono (JETL (Journal of Education, Teaching and Learning), 2019)
In the 2003 National Education System Law, education is a conscious and planned effort to realize a learning atmosphere and learning process so that students actively develop their potential to have spiritual strength, self-control, personality, intelligence, noble character, and skills. it needs itself, society, nation, and country. Educational goals in Indonesia shape the noble character of students. To realize that, fairytale learning is one of them that can be used. It examines the values contained in fairy tales, so research is conducted. The form of this research is qualitative, and the research method is a description. Data collection techniques study documents. Fairy tales that are used as data sources accessed on the internet and storybooks. The sociology of literature approach is used to analyze data. Fairy tale oral literature has values that can be used to instill positive character in students. The values that are reflected in the fairy tales studied are the values of caring for the environment, thinking wisely before acting, the greedy nature of bringing disaster. The activity of appreciating fairy tales is closely related to training to sharpen feelings, reasoning, and imagination, as well as sensitivity to society, culture and the environment. Students are expected to be able to enjoy, appreciate, understand, and utilize literary works to develop their personality, broaden their horizons, and improve their knowledge and language skills. With a lot of reading literary works will help students become cultured humans who are responsive to noble values in social life. Students who are cultured are expected to be great human beings but still simple, free but self-controlled, strong but full of tenderness.